Correlations of leuko-araiosis with cerebral atrophy and perfusion in elderly normal subjects and demented patients. - Kawamura, J (1993)
CT images of leuko-araiosis in brain slices were quantified according to volumes of reduced Hounsfield units in frontal periventricular white matter in groups of elderly patients with multi-infarct dementia (MID, n = 23) and dementia of the Alzheimer type (DAT, n = 16). Volumes of leuko-araiosis, estimates of atrophic cerebral tissue, and local cerebral perfusion utilising inhalation of xenon gas as the indicator were correlated on the same CT slices. Ratios of frontal leuko-araiosis to total brain tissue volume were similar for patients with MID and DAT (mean 5.7 (SD 2.1)% v 6.5 (3.2%)), and both were significantly greater than ratios in elderly normal volunteers (3.1(1.3)%, 0 < 0.001). Cerebral atrophy (measured as the ratio of volumes of cerebrospinal fluid to total brain area) for DAT patients was 17.0 (6.7)%, which was greater than for MID patients (12.5 (5.4)%; p < 0.05) and both types of patients showed more cerebral atrophy than did age matched, elderly normal subjects. Cerebral perfusion was decreased in all regions measured in patients with MID and DAT compared with elderly normal subjects. Multi variate regression analyses correlated frontal leuko-araiosis with reductions of local cerebral blood flow in subcortical grey matter (p < 0.025) in patients with vascular dementia but not in those with DAT. These quantitative measures implicate decreased perfusion due to atherosclerosis in territories supplied by the deep penetrating cerebral arteries in the pathogenesis of leuko-araiosis in patients with vascular dementia, but suggest a different pathogenesis for leuko-araiosis in Alzheimer's disease.